Ecological-Themed POEW in English for Biology Academic Writing: A Mixed-Methods Pilot Study with Repeated Measures - Sianna Sianna; Nurzakiyah R; Khadijah Maming; Ilham Sahabuddin; Wahyuddin; Nurmadinah (Universitas Sulawesi Barat, 2026)
Academic writing poses persistent challenges for biology education students, who must navigate English accuracy, paragraph organization, and scientific reasoning simultaneously. This pilot mixed-methods study with repeated measures examined the implementation of an ecological-themed Predict-Observe-Explain-Write (POEW) model in an English for Biology course and explored students' perceptions of the learning process. Eight second-semester Biology Education students at Universitas Muhammadiyah Parepare, Indonesia, participated in a one-group repeated-measures design. The intervention comprised four 100-minute sessions, each addressing a distinct ecological theme (ecosystems, food chains/food webs, biodiversity, and environmental issues). Students completed academic paragraph-writing tasks at four time points (pretest, midtest, posttest, and two-week follow-up) and were scored using the ESL Composition Profile, while semi-structured interviews provided qualitative data analyzed thematically. The Friedman test revealed a significant difference across the four measurements, χ²(3) = 18.75, *p* < .001, Kendall's W = .78. Wilcoxon signed-rank tests indicated significant gains from pretest to posttest (Z = -2.521, *p* = .012) and from pretest to follow-up (Z = -2.394, *p* = .017), though the posttest-to-follow-up decline was not significant (Z = -1.751, *p* = .080). Interview data yielded three themes: vocabulary and pronunciation support, improved paragraph organization and idea mapping, and difficulties during the prediction stage due to limited ecological vocabulary. Theoretically, this study contributes to the integration of inquiry-based learning principles with ESP pedagogy by demonstrating how a staged cognitive sequence (POEW) can reduce the cognitive load of L2 academic writing. Practically, it offers a replicable instructional framework for EFL lecturers teaching scientific writing in biology education, with a specific emphasis on vocabulary scaffolding prior to prediction activities.